Plastic response by a small cervid to supplemental feeding in winter across a wide environmental gradient. Issue 1 (24th January 2017) - Ossi, Federico; Gaillard, Jean‐Michel; Hebblewhite, Mark; Morellet, Nicolas; Ranc, Nathan; Sandfort, Robin; Kroeschel, Max; Kjellander, Petter; Mysterud, Atle; Linnell, John D. C.; Heurich, Marco; Soennichsen, Leif; et al.
Abstract: Supplemental feeding for ungulates is a widespread practice in many human‐dominated landscapes across Europe and North America, mainly intended to seasonally support populations. Surprisingly, little consideration was given so far to the effect of supplemental feeding on ungulate spatial ecology at a large scale, in management and conservation studies. Analyses of the main ecological drivers influencing the use of supplemental feeding sites by ungulates across a gradient of abiotic and biotic factors are currently lacking. We conducted a large‐scale assessment of ecological and management drivers of use of feeding station sites in roe deer ( Capreolus capreolus ), a small cervid widely distributed across Europe that is particularly sensitive to winter severity. We tested four competing hypotheses by comparing the time spent at feeding station sites by 180 individual Global Positioning System‐collared roe deer from nine populations spanning a wide latitudinal and altitudinal gradient. We found that roe deer used feeding station sites highly opportunistically in response to winter severity across its range. The harshest weather conditions at the northern range limit or the highest elevations provoked an intense use of feeding station sites, which typically peaked at the end of winter, in accordance with the adverse weather and nutritional condition hypotheses. Consistently, milder winters corresponded to a reduced and/or more homogeneous use of supplemental feeding. In general, intensively used feeding station sites heavily conditioned spatial behavior of roe deer. Importantly, biotic factors such as the presence of competitors decreased roe deer use of supplemental feeding station sites. Our results emphasize the importance of this human‐induced alteration to resource distribution, especially in the context of the rapidly occurring climate change that is modifying resource availability for ungulate populations.